PENYELENGGARAAN JAMINAN SOSIAL SEBAGAI TUGAS PEMERINTAHAN - H. Yacob Djasmani (Faculty of Law, Universitas Diponegoro, 2011)
Based on Social lnsurence Act, Implementation of Social lnsurence is a government duty. Its realized by a executing body that have right and duties based on administrative law. Based on the Administrative Law, The Government responsible to execute it caused based on 1945 Constitution, the social insurence is a part of The Human Rights.